MANAJEMEN PEMBELAJARAN BERBASIS PROYEK (PROJECT BASED LEARNING) PADA PROGRAM KETERAMPILAN - Sumarnie; Ernawatie; Setiawan (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2023)
The purpose of writing this article is to examine Project Based Learning Management in the Skills Program at SLBN 1 Palangka Raya. This research method uses a qualitative approach, primary and secondary data sources, data collection techniques namely interviews, observation and document study. Data analysis used interactive data analysis, including: data reduction, data presentation and drawing conclusions. The results of the study show that Project Based Learning is very good and effective in the Skills Program, proven in its implementation to be able to foster student motivation and creativity both individually and in groups in completing all assigned tasks so that the products produced are of very good quality and variety awards that have been obtained in competitions related to the skills program.